Investigation of velocity profile in time dependent boundary layer flow of a modified power-law fluid of fourth grade - Yürüsoy, Muhammet (Zielona Góra: Uniwersytet Zielonogórski)
This paper deals with the investigation of time dependent boundary layer flow of a modified power-law fluid of fourth grade on a stretched surface with an injection or suction boundary condition. The fluid model is a mixture of fourth grade and power-law fluids in which the fluid may display shear thickening, shear thinning or normal stress textures.
Keywords: boundary layer equations; power-law fluids; fourth grade fluids